Analysis of the Exeter V40 femoral stem prosthesis fracture: systematic review and single centre case series - Joshua W. Thompson; James Corbett; Daniel Bye; Adrian Jones; Elizabeth K. Tissingh; John Nolan (Bone & Joint Open, 2021)
Aims: The Exeter V40 cemented polished tapered stem system has demonstrated excellent long-term outcomes. This paper presents a systematic review of the existing literature and reports on a large case series comparing implant fractures between the Exeter V40 series; 125 mm and conventional length stem systems. Methods: A systematic literature search was performed adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. In parallel, we performed a retrospective single centre study of Exeter V40 femoral stem prosthetic fractures between April 2003 and June 2020. Results: There are 25 reported cases of such prosthetic fractures confined to small case series and case reports within the literature. We report an additional 19 cases to the literature (mean age 66.3 years (SD 11.7); 12 (63%) females; BMI 32.9 kg/m2 (SD 5.9)). The mean time from index procedure to fracture was 7.8 years (SD 3.6; 2.5 to 16.3). Exeter V40 stem fracture incidence was 0.15% and 1.21% for primary and revision arthroplasty, respectively. Incidence was significantly higher in revision arthroplasty (p < 0.001) and 125 mm length stems compared to ≥ 150 mm length stems (1.25% vs 0.13%, respectively; p < 0.001). When comparing different stem length cohorts, 125 mm short-stems were associated with stem-body fractures (92% vs 29%; p = 0.0095), earlier time to fracture (6.2 years vs 11.0 years; p = 0.0018), younger patient age at time of fracture (62.7 years vs 72.6 years; p = 0.037), and female sex (75% vs 43%; p = 0.326). Conclusion: This complication remains rare, although we report a significantly higher incidence at up to 17 years follow-up than in the literature. Short 125 mm length Exeter V40 stems undoubtedly have a role in restoring anatomy and biomechanics in smaller femoral geometries, although the surgeon has to appreciate the higher risk of stem fracture and the associated predisposing factors which may necessitate particular attention to surgical technique and planning.